Design of a halogen bond catalyzed DNA endonuclease - Margaret G. Walker; Cesar Gustavo Mendez; Alexander N. Ho; Ryan S. Czarny; Anthony K. Rappé; Pui Shing Ho (Proceedings of the National Academy of Sciences, 2025)
In this study, we expand the repertoire of biological catalysts by showing that a halogen bond (X-bond) can functionally replace the magnesium (Mg 2+ ) cofactor in mouse endonuclease G ( m EndoG). We mutated the metal coordinating glutamate E136 in m EndoG to a meta- halotyrosine ( m X Y, X = chlorine or iodine) to form a m X Y- m EndoG construct that is both acid and base catalyzed. Under basic conditions, the enzyme is inactivated by the metal chelator ethylene diamine tetraacetic acid (EDTA), indicating that the halogen substituent facilitates deprotonation of the tyrosyl hydroxyl group, allowing recruitment of Mg 2+ to restore the metal-dependent catalytic center. At low pHs, we observe that the m X Y- m EndoG is resistant to EDTA inactivation and that the iodinated constructed is significantly more active than the chlorinated analogue. These results implicate a hydrogen bond (H-bond) enhanced X-bond as the catalyst in the m X Y- m EndoG, with asparagine N103 serving as the H-bond donor that communicates the protonation state of histidine H104 to the halogen. This model is supported by mutation studies and electrostatic potential (ESP) calculations on models for the protonated and unprotonated m X Y···N103···H104 system compared to the Mg 2+ coordination complex of the wild type. Thus, we have designed and engineered an enzyme that utilizes an unnatural catalyst in its active site—a catalytic X-bonding enzyme, or cX- Zyme—by controverting what constitutes a metal catalyst in biochemistry.